Cognitive and communicative approaches to linguistic analysis - Contini-Morava, Ellen, 1948-; Kirsner, Robert S., 1941-; Rodriguez-Bachiller, Betsy (Studies in functional and structural linguistics ;, 2004)
This volume is the product of a Columbia School Linguistics Conference held at Rutgers University in October 1999, where the plenary speaker was Ronald W. Langacker, a founder of Cognitive Linguistics. The goal of the book is to promote two kinds of dialogue. First, dialogue between Cognitive Grammar and the particular sign-based approach to language known as the Columbia School. While they share certain basic assumptions, the "maximalist" CG and the "minimalist" CS differ both theoretically and methodologically. Given that philosophers from Mill to Kuhn to Feyerabend have stressed the importa